Lessons learned from the ESPN/ERA-EDTA Registry - Harambat, Jérôme; Schaefer, Franz (Pediatric nephrology, 2015)
End-stage renal disease (ESRD) in children is a medically challenging condition. Due to its rarity and special features, methodologically sound collaborative studies are required. In 2007, a new European registry of pediatric renal replacement therapy (RRT), the ESPN/ERA-EDTA Registry, was launched. In recent years, the Registry has provided comprehensive data on incidence, prevalence, patient characteristics, RRT modalities, and mortality in pediatric ESRD, along with relevant insights into cardiovascular risk, anemia, nutrition and growth, transplantation outcomes, and rare diseases. In this review, we describe the study design and structure underlying the ESPN/ERA-EDTA Registry, summarize the major research findings from more than 20 publications, and discuss current limitations and the future challenges to overcome.